Near-infrared boosted ROS responsive siRNA delivery and cancer therapy with sequentially peeled upconversion nano-onions. (December 2019) - He, Yuling; Guo, Shuwen; Wu, Lina; Chen, Pengwen; Wang, Leyong; Liu, Ying; Ju, Huangxian
Abstract: RNA interference (RNAi) therapy has become an appealing approach for cancer treatment, while the specificity and efficiency of controlled small interference RNA (siRNA) release remain challenging due to the heterogeneity of tumor environment. Herein, upconversion nano-onions (UCNOs) with stacked polymer coating layers are constructed to decompose sequentially in response to extracellular environment and NIR stimulation. The UCNOs (UCNPs-PEIRB-PEISeSe/siRNA-R8-HA) are composed of upconversion nanoparticles (UCNPs) core functionalized with inner coating layer of photosensitizer rose bengal (RB) conjugated PEI 600, middle coating layer of singlet oxygen ( 1 O2 ) sensitive diselenide linked PEI 600 with therapeutic siRNA loading and cell-penetrating peptide R8 modification, and outer coating layer of negatively charged hyaluronic acid (HA). HA prevents siRNA leakage during delivery process and specifically targets tumor cells with overexpressed CD44 membrane receptors, and digested by cell secreted hyaluronidase (HAase). Upon the subsequent irradiation at 808 nm, UCNPs core generates emissions around 540 nm, which activate RB to boost ROS generation for complete PEI-SeSe decompose. The NIR boosted decompose of UCNOs induces a fast and efficient siRNA release, which effectively improves the gene silencing efficiency in vitro and suppresses tumor growth in vivo . The proposed sequentially responsive UCNOs have promising potential application in precision medicine. Graphical abstract: Upconversion nano-onions sequentially peeled in response to tumor microenvironment and NIR to boost intracellular ROS concentration for efficient siRNA release and therapy.Image 1 Highlights: Sequentially responsive UCNOs are proposed with stacked polymer coating layers for gene therapy. Inner layer PEI-RB boosts ROS generation intracellularly in response to external NIR stimuli. Middle layer PEI-SeSe completely decomposes in response to ROS for high efficient siRNA release. Outer layer HA decomposes in tumor microenvironment to provide siRNA delivery specificity.